Analysis of Process Parameters for Composites Manufacturing using Vacuum Infusion Process. (2020) - Gajjar, Tushar; Shah, Dhaval B.; Joshi, S.J.; Patel, K.M.
Abstract: Vacuum infusion process (VIP) is the versatile process for the preparation of large composite parts due to low cost and highly accurate manufacturing method. The carbon fiber reinforced polymer (CFRP) is widely used in space applications, automobile, aerospace and sports industries because of good specific properties over conventional metals and alloys. In this research paper, flat plates from CFRP have been manufactured using VIP by considering various process parameters. The part thickness and resin pressure have been considered as processing parameters in flat plate manufacturing. The compaction pressure and volume fraction have been measured at different locations on the flat plate during manufacturing. The compaction pressure is also simulated in FLUENT software for all manufactured parts and compared with experimental results. The percentage variation of resin pressure for experimental and simulation results are found within the good agreement. The thickness of the part is decreasing whereas the volume fraction is increases from the resin inlet to the resin outlet.